Hibberdia magna (Chrysophyceae): a promising freshwater fucoxanthin and polyunsaturated fatty acid producer - Střížek, Antonín; Přibyl, Pavel; Lukeš, Martin; Grivalský, Tomáš; Kopecký, Jiří; Galica, Tomáš; Hrouzek, Pavel (Microbial cell factories, 2023)
BACKGROUND: Algae are prominent producers of carotenoids and polyunsaturated fatty acids which are greatly prized in the food and pharmaceutic industry. Fucoxanthin represents a notable high-value carotenoid produced exclusively by algae. Its benefits range far beyond just antioxidant activity and include cancer prevention, anti-diabetes, anti-obesity, and many other positive effects. Accordingly, large-scale microalgae cultivation to produce fucoxanthin and polyunsaturated fatty acids is still under intensive development in the commercial and academic sectors. Industrially exploitable strains are predominantly derived from marine species while comparable freshwater fucoxanthin producers have yet to be explored. RESULTS: In this study, we searched for freshwater fucoxanthin producers among photoautotrophic flagellates including members of the class Chrysophyceae. The initial screening turned our attention to the chrysophyte alga Hibberdia magna. We performed a comprehensive cultivation experiments using a temperature × light cross-gradient to assess the impact of these conditions on the target compounds productivity. Here we present the observations that H. magna simultaneously produces fucoxanthin (max. 1.2% dry biomass) and polyunsaturated fatty acids (max. ~ 9.9% dry biomass) and is accessible to routine cultivation in lab-scale conditions. The highest biomass yields were 3.73 g L-1 accompanied by maximal volumetric productivity of 0.54 g L-1 d-1 which are comparable values to marine microalgae fucoxanthin producers in phototrophic mode. H. magna demonstrated different optimal conditions for biomass, fucoxanthin, and fatty acid accumulation. While maximal fucoxanthin productivities were obtained in dim light and moderate temperatures (23 °C× 80 µmol m-2 s-1), the highest PUFA and overall biomass productivities were found in low temperature and high light (17-20 °C × 320-480 µmol m-2 s-1). Thus, a smart biotechnology setup should be designed to fully utilize H. magna biotechnological potential. CONCLUSIONS: Our research brings pioneer insight into the biotechnology potential of freshwater autotrophic flagellates and highlights their ability to produce high-value compounds. Freshwater fucoxanthin-producing species are of special importance as the use of sea-water-based media may increase cultivation costs and prohibits inland microalgae production.
Keywords: xanthofyly; nenasycené mastné kyseliny; Chrysophyceae; mikrořasy; Fatty Acids; Carotenoids; karotenoidy; Xanthophylls; Polyunsaturated fatty acids; Chrysophyta; Light and temperature effect; Hibberdia magna; mastné kyseliny; Volumetric productivity; Biomass; Fatty Acids, Unsaturated; Microalgae; Fucoxanthin; biomasa